Efektifitas Strategi Mastery Learning dalam Meningkatkan Kemampuan Vokasional Membuat Llilin Berbagai Aroma bagi Anak Tunarungu - Devi, Saebrina; Efendi, Jon (Jurnal Penelitian Pendidikan Khusus, 2022)
This study discusses how skills learning activities at SLBN 2 Padang are still lacking in the latest innovations so that children tend to experience boredom in carrying out casual skills learning. Seeing from these problems, the author tries to teach making different types of vocational skills and ways of teaching namely presenting vocational skills in making candles of various aromas which are included in the category of souvenir vocational skills. This study uses experimental research methods. This study uses a mastery learning strategy as a learning method. This study aims to determine whether the mastery learning strategy is effectively used in improving vocational skills in making candles of various scents for deaf children in class IX at SLBN 2 Padang consisting of 2 girls and 3 boys. The results of this study are an increase in children's ability to make candles of various aromas after being given treatment using a mastery learning strategy, as evidenced by the Wilcoxon Sign Rank Test, the resulting value is 2,041 with probability and Asymp sign. (2- tailed) = 0.042 so the probability obtained is 0.041.